Analisis Kesalahan Peserta Didik dalam Merepresentasikan Penyelesaian Soal Hukum Archimedes - Florentina Dwi Astuti (Journal on Education, 2023)
Physics Learning is always related to mathematical calculations problem. In this study it could be seen that students have mistakes that made them couldn’t solve physics questions correctly. The physical mistakes which consist of representing verbal and physical as well as mathematical mistakes in representing problem solving in form of mathematical became the evidence that students have not completely understood the concept of Archimedes' law and not only mathematical problems that affected the solving Archimedes' law questions. In this qualitative research, which aimed to look at student mistakes in representing the completion of Archimedes' law questions, verbal representation results were obtained with the students’ mistake average was 60%, then there were mathematical mistakes with the students’ percentage was 44% and finally physical mistakes was 33%